Dinamika Dakwah al-Jam’iyatul Washliyah di Tanah Batak Toba, Sumatera Utara: The Dynamics of al-Jam’iyatul Washliyah Da’wah in the Toba Batak Land, North Sumatra - Ilyas, Sopian; Abdul Kadir, Fakhrul Adabi (Jurnal Usuluddin, 2021)
The Toba Batak Land is one of the provinces in North Sumatra, where the majority of the population are Christians. This region is one of the localities for Islamic preaching in North Sumatra. Interestingly, Indonesian Muslims have long been active in developing Islamic teachings in the Land of Batak Toba through da’wah efforts. This da’wah effort continues, from ancient times to the present, by sending preachers initiated by the al-Washliyah organization. This organization is active in the field of da’wah, especially in sending preachers to deliver Islamic sermons in Batak Toba. Evidently, this organization has contributed a lot to the spread of Islam in this land. This study will discuss the dynamics of da’wah in the Batak Land of Toba. The method used is historical research (historiography). Based on this study, it can be known that the da’wah movement in Tanah Batak Toba is led by al-Washliyah organization, which is carried out through the sending of its preachers to Tanah Batak Toba until now, through Sahabat Dakwah Pemuda Samosir under the al-Washliyah organization. In its development, the da’wah effort in Tanah Batak Toba is in dire need of the support of Muslims, both in material form and in quantity in the delivery of sending the preachers.